Lí thuyết về chuẩn ngôn ngữ và vấn đề chuẩn chính tả tiếng Việt. /Bùi Khánh Thế. - Bùi, Khánh Thế.
Language standardization in general and spelling standardization in particular has always been an issue of special concern in Vietnam, especially after the decision "to use Vietnamese in all levels of the national education" was made. Within the debates on Vietnamese standardization, some topics have attracted much attention from researchers as no consensus in terms of their scientific basis and practical application has been reached. The Constitution of the Socialist Republic of Vietnam issued in 2013 was a milestone in the development of the Vietnamese language. For the first time Vietnamese language was legally recognized "the national language" in Article 5, section 3... It is time to think about a language law for the national language. In that legislation, spelling problems of the national language will have a proper place. This article is a contribution to the debate on the language policy in Vietnam.